The Influence of Personal Brand on Service Brand through the Use of Networking - Popa, Florentina (Acta Universitatis Danubius. Communicatio, 2022)
The Internet offers both communication and public relations specialists and entrepreneurs a multitude of opportunities to increase their notoriety and interact with stakeholders. Many of the PR strategies in the online environment use interview-type videos in which the creator wants to cultivate his personal brand with the help of guests who already have notoriety and through the topics covered. If in most cases the entrepreneurs are invited, there is also the possibility for the entrepreneur to take on this role as a creator of materials to cultivate his personal brand, which he associates with the company brand. It is an interesting tactic that provides visibility, but gaining credibility is a difficult road that requires planning, clarity and consistency of messages and above all respecting the values ​​claimed by the entrepreneur. The paper aims to analyze how this communication and public relations strategy manages to achieve its goal and highlight the threats that can affect the personal brand of the storybrand hero.